Strategi Sosialisasi Model Crowdfunding Sebagai Alternatif Penghimpunan Dana Zakat Infak Sedekah Pada Dompet Dhuafa Sulawesi Selatan - Ridwanto; Mukhtar Lutfi; Abdul Wahid Haddade (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Crowdfunding model emerged as an alternative to collect ZIS funds in the digitalization era with technological developments and changes in donor behavior. This research aimed to explore the strategy of socializing the Crowdfunding model as an alternative for collecting ZIS funds in Dompet Dhuafa, South Sulawesi. This research used qualitative methods with a phenomenological approach to explore how individuals interpret the socialization strategy of the Crowdfunding model by Dompet Dhuafa South Sulawesi. Data collection methods included in-depth and structured interviews, observation, and documentation. The research results showed that Dompet Dhuafa South Sulawesi used three main methods in socializing the Crowdfunding model: placing advertisements and videos on Kitabisa.com platform, using social media such as Instagram and Facebook, and placing banners in strategic places. However, the research suggested the need to add other methods of outreach such as outreach in the community and seminars on universities, to expand the reach and effectiveness of Crowdfunding campaigns. It is hoped that the results of this research provided a practical contribution to Dompet Dhuafa South Sulawesi in optimizing the collection of ZIS funds through online platforms and provided academic insight into the study of Islamic economics, especially on ZIS management.